Eugenia erythrosepala, a new species of Eugenia sect. Umbellatae (Myrtaceae) from the Atlantic Forest of Southeastern Brazil, and notes on Eugenia longibracteata - Maruyama, Adriano Da Silva De Cicco; Valdemarin, Karinne Sampaio; Silva, Mariana Andreotti Bueno Da; Guilherme, André; Medeiros, Alexandre Da Silva; Mazine, Fiorella Fernanda (Phytotaxa, 2026)
Eugenia P.Micheli ex L. is the largest genus of Myrtaceae in the Neotropics, with Brazil representing its main center of diversity. During fieldwork conducted in high-altitude Dense Ombrophilous Forest of the Serra do Mar State Park (Núcleo Cunha), São Paulo, Brazil, previously unidentified specimens were recognized as a new species of Eugenia sect. Umbellatae. Here we describe and illustrate Eugenia erythrosepala, and provide taxonomic comments, a distribution map, a preliminary conservation assessment, and an identification key to related species. The new species is morphologically similar to Eugenia adenantha, sharing glabrous branches and leaves, markedly canaliculate petioles, elliptic leaf blades with an acuminate apex, 8–14 pairs of secondary veins, two marginal veins, persistent bracteoles, and single-seeded fruits. It differs, however, by its shrubby habit up to 1.8 m tall (vs. a tree up to 16 m tall), smaller leaves 3–6 cm long (vs. 6.5–10 cm), longer pedicels 18–20 mm (vs. 3–15 mm), and fewer ovules per locule, 3–5 (vs. 12–22). Eugenia erythrosepala is also morphologically similar to E. gracillima, sharing glabrous branches and leaves, elliptic leaves with 9–14 pairs of secondary veins, inflorescences with late vegetative growth, and persistent bracteoles in fruits. It is distinguished by its membranaceous leaf blades (vs. chartaceous), secondary veins inserted at 45–55° (vs. 60–70°), triangular glabrous bracts (vs. ovate to lanceolate and slightly puberulous), orbicular to deltoid bracteoles (vs. ovate), sepals orbicular with acute apex (vs. ovate-oval with rounded apex), longer filaments 6–8 mm (vs. up to 5.5 mm), longer styles 9–11 mm (vs. 5–6 mm), longer pedicels 18–20 mm (vs. 7–18 mm), and ovoid to ellipsoid fruits (vs. globose). The species is currently known from two nearby localities above 1,100 m a.s.l. in riparian environments and is preliminarily assessed as Data Deficient (DD) according to IUCN criteria due to limited sampling and restricted records. Additionally, we provide the first description of the fruits of Eugenia longibracteata and present an updated conservation assessment for this species, now classified as Critically Endangered (CR) based on its restricted distribution, small area of occupancy, and current anthropic and natural threats.